2007
DOI: 10.1158/1535-7163.mct-06-0741
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescent labeled anti–epidermal growth factor receptor antibody to image head and neck squamous cell carcinoma xenografts

Abstract: Physicians and surgeons rely on subtle tissue changes to detect the extent of tumors and the presence of residual disease in the clinical setting. The development of a cancer-specific fluorescent contrast agent has the potential to provide real-time tumor imaging in the clinic or operating room. Because epidermal growth factor receptor (EGFR) is highly overexpressed on the surface of head and neck squamous cell carcinoma (HNSCC), we sought to determine if fluorescently labeled anti-EGFR antibody could be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 25 publications
0
63
0
Order By: Relevance
“…This information adds to the recent data obtained for fluorescence-labeled antibodies targeting the epidermal growth factor receptor (EGFR), HER2, and the insulin-like growth factor receptor 1 (IGF-1R) (23)(24)(25)(26). Cetuximab labeled with the NIR fluorescent dye Cy5.5 showed specific tumor uptake in head and neck squamous cell carcinoma xenografts (23), whereas the IGF-1R targeting antibody AVE-1642 labeled with the NIR fluorescent dye Alexa 680 was specifically taken up by the R-/IGF-1R xenograft tumor (24).…”
Section: Discussionmentioning
confidence: 81%
“…This information adds to the recent data obtained for fluorescence-labeled antibodies targeting the epidermal growth factor receptor (EGFR), HER2, and the insulin-like growth factor receptor 1 (IGF-1R) (23)(24)(25)(26). Cetuximab labeled with the NIR fluorescent dye Cy5.5 showed specific tumor uptake in head and neck squamous cell carcinoma xenografts (23), whereas the IGF-1R targeting antibody AVE-1642 labeled with the NIR fluorescent dye Alexa 680 was specifically taken up by the R-/IGF-1R xenograft tumor (24).…”
Section: Discussionmentioning
confidence: 81%
“…Although not addressed in the current study, we have previously shown that fluorescently labeled cetuximab is specific for primary tumors and demonstrates significantly higher fluorescence compared with human epithelial background (xenografted human skin grafts). 8 These results suggest that this technology could be used to facilitate transoral laser or robotic cases for primary tumors.…”
Section: Discussionmentioning
confidence: 91%
“…However, previous studies using the technique on human skin grafts did not demonstrate any detectable fluorescence. 8 Because this was a pilot study to demonstrate the feasibility of the imaging technique for detection of metastasis, a relatively small number of mice were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resection of the tumours was carried out under guidance of near-infrared fluorescence imaging, enabling identification of any remaining cancerous cells in situ [30]. In addition, further studies have utilised optical imaging to detect cervical node metastases in orthotopic mouse models as all nodes that showed a fluorescent signal were found to be malignant metastases from squamous cell carcinoma [31,32]. Thus, near-infrared fluorescence imaging can be used to delineate tumour margins and any malignant cells remaining post resection, making it an invaluable tool for animal model imaging.…”
Section: Optical Imagingmentioning
confidence: 99%